2014
DOI: 10.12973/eurasia.2014.1084a
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Learning in Chemistry Classes

Abstract: Currently not many people would doubt that computers play an essential role in both public and private life in many countries. However, somewhat surprisingly, evidence of computer use is difficult to find in German state schools although other countries have managed to implement computer-based teaching and learning in their schools. This paper attempts to understand the reasons for this phenomenon and to show that more research and development on computer-based teaching and learning should be done. It starts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
10
0
3
Order By: Relevance
“…teacher education programmes), the current capacity of these universities has been increasing year by year and exposing to crowded classes. Ferreira et al, 2013;Çalık et al, 2014a, 2014b, 2015Pietzner, 2014). chemists) use of the chemistry laboratory and inquiry-based methods.…”
Section: Implications For Practice and Learningmentioning
confidence: 99%
“…teacher education programmes), the current capacity of these universities has been increasing year by year and exposing to crowded classes. Ferreira et al, 2013;Çalık et al, 2014a, 2014b, 2015Pietzner, 2014). chemists) use of the chemistry laboratory and inquiry-based methods.…”
Section: Implications For Practice and Learningmentioning
confidence: 99%
“…Computer-based learning is another technique used in the chemistry teaching and learning process in secondary schools for several chemistry-related subtopics. Research conducted in German secondary schools revealed that the chemistry subtopics of chemical bonding, chemical equilibrium, the structure of matter, organic reaction mechanisms and electrochemistry can be taught using computer-based learning techniques (Pietzner, 2014). However, according to Paulson (2009), students do much better in the organic chemistry subtopic when they are able to have many open-ended discussions during the teaching and learning process as opposed to only having the teacher talk.…”
Section: Introductionmentioning
confidence: 99%
“…One of the cooperative learning models that can be applied to increase the students' problem-solving abilities is learning through advanced organizer model. Advance organizer model is a short presentation of visual and verbal information that does not contain any specific content or material of new material to be studied (Atomatofa, 2013;Chuang & Liu, 2014;Nurhayati, 2017;Pietzner, 2014). The application of this learning model has been done by several researchers and gives positive impact in improving students' learning outcomes (Panggabean, 2013;Silaban & Napitupulu, 2016).…”
Section: Introductionmentioning
confidence: 99%